That Should Be Left to Doctors, That's What They are There For! - Exploring the Reflexivity and Trust of Young Adults When Seeking Health Information - Mendes, Á (2017)
This paper explores the health information-seeking practices of healthy young adults and how they assess and rank sources of information through a qualitative study. The findings show that participants (a) are strongly committed to searching for information about health and lifestyle, especially via the Internet; (b) healthcare professionals were perceived as the most reliable source of health information and advice; (c) online health information, although frequently accessed and experienced as empowering, is seen as a potentially unreliable source. Findings evidence how becoming better informed about health-related topics plays a pivotal role in individuals’ lives, most notably by using the Internet. Participants were able to reflect about what it means to know about health. The construction of trust regarding health information involved a heuristic process vis-à-vis source reliability and perceived credibility that places doctors as the most trustworthy medium of medical advice and health information. We conclude that participants’ trust toward professionals suggests the preference and need for more personalized care; and it is a response to the ambiguity and uncertainty that permeates the health information landscape, particularly that which is web-based.